Design of Android-Based Augmented Reality Media for Teaching Computer Network Models - Novaliendry, Dony; Irnanda, Muhammad Fakhri; Budayawan, Khairi; Asmara, Delvi (Jurnal Teknologi Informasi dan Pendidikan, 2025)
The development of digital technology has a major impact on the education sector, especially since the Covid-19 pandemic changed the learning system to online. One technology that has great potential in supporting the learning process is Augmented Reality (AR). This technology allows the integration of two or three-dimensional virtual objects into the real environment interactively. This study aims to design and build Android-based learning media with marker-based AR technology for the introduction of computer network models for class XI at SMA Negeri 4 Padang. Based on the results of observations and interviews with informatics teachers, it is known that learning is still dominated by theory without direct visualization of computer network devices due to limited practical tools. The learning media developed uses AR technology with markers as markers to display 3D objects, utilizing the Vuforia platform, 3D models are created using Blender, interface design using Figma, and system integration is carried out with Unity. The visualized material includes network topology (bus, star, ring, mesh) and the OSI Layer model. With this media, students can understand the concept of computer networks more interactively and deeply, and increase their involvement in the learning process.